Organizações e espaços da raça no oeste paulista: movimento negro e poder local em Rio Claro (dos anos 1930 aos anos 1960) - Pereira, Flávia Alessandra de Souza (2008)
In Organizações e Espaços da Raça no Oeste Paulista: Movimento Negro e Poder Local em Rio Claro (dos anos 1930 aos anos 1960) (Organizations and Spaces of Race in Western São Paulo State, Brazil: The Black Movement and Local Government in Rio Claro [from the 1930s to the 1960s] ) we try to comprehend the profile and shape of the black movement of the city of Rio Claro, and relations between this movement and the local government with regard to specifically racial demands. We focus on black spaces of sociability of Rio Claro, giving special attention to the identitary processes that shaped this sociability, and also to the demands that black actors addressed to the local government as part of the struggle for their own spaces of race in a white majority context, we emphasize, deeply marked both by open racism against blacks and by the impermeability of the local political system to blacks in general. It was in this context that the local black movement developed, over the course of decades, the basis for its collective mobilization for the long-desired house of its own a house that was materialized in its two social headquarters, finally built at the end of the 1960s. This research was supported by FAPESP (São Paulo State Research Fundation, Brazil, regular doctoral scholarship) and by CAPES (Coordination for the Improvement of Higher Education Personnel, Brazil, for foreign doctoral studies).